IMPLIKASI MODERNISASI TERHADAP PERMAINAN TRADISIONAL PADA ANAK-ANAK DAN REMAJA (STUDI DI DESA GUALI KECAMATAN KUSAMBI KABUPATEN MUNA BARAT) - Jaya, Rahmat; Baka, Wa Kuasa; Aso, La (Jurnal Penelitian Budaya, 2021)
Abstract: The objective of this study is to describe the implications of modernization on traditional games for children and adolescents in Guali Village, Kusambi District, West Muna Regency. This research uses a qualitative descriptive approach. Subjects in this study were determined by purposive snowball that is the samples were obtained through a rolling process from one respondent to another and were usually used to explain the social or communication (sociometric) patterns of a particular community. Data collection techniques in this study were carried out by observation, interviews, and documentation. The results of this study indicate that the implications of modernization on traditional games for children and adolescents in Guali Village, Kusambi District, West Muna Regency are as follows: (a) economic implications, (b) health implications, (c), social implications, and (d) implications of the loss of creative ideas.Keywords: Implication, moderenization, traditional games, children and adolescents